Modele myślenia o reformowaniu oświaty - Kwieciński, Zbigniew (Wydawnictwo Naukowe UAM, 2012)
Autor analizuje siedem głównych modeli (wzorów, paradygmatów) o reformowaniu systemów oświaty: pedagogizm, reformizm, podejście systemowe, podejście dialektyczne, sceptycyzm (socjologizm), odszkolnienie (deschooling), eklektyzm (reformy pozorowane), ukazuje główne różnice i podobieństwa.

Author analyses seven main models of reflections (paradigms, patterns) on educational reforming: pedagogism, reformism, systemic approach, dialectic approach, scepticism (sociologism), deschooling, eclectism (simulated reforms). The author presents main differences and similarities.
Models of reflection on educational reforming
Keywords: reforma oświaty; education system reform; cele szkoły; aims of education; utopie edukacyjne; educational utopias; paradygmaty myślenia edukacyjnego; paradigms of educational thinking; Neodidagmata